The Report of the Working Group on Hill Area Development Programme for the Seventh Five Year Plan 1985-90 - Planning Commission (Planning Commission, 1985)
Awareness of the importance of ecology in this country dawned in later, though the planning process started soon after Independence in the early fifties. The realisation has been growing that man has been pushing his geo-environmental frontiers, as a result of which the boundaries of the planning process have also to be pushed farther. The perception of nature in the mind of man has also been undergoing transformation. Instances of assaults on nature are not infrequent.
Planning Commission
Planning Commission